India Shining and Bharat Drowning : Comparing Two Indian States to the Worldwide Distribution in Mathematics Achievement - Das, Jishnu (World Bank, Washington, DC, 2012)
This paper uses student answers to publicly released questions from an international testing agency together with statistical methods from Item Response Theory to place secondary students from two Indian states -Orissa and Rajasthan -on a worldwide distribution of mathematics achievement. These two states fall below 43 of the 51 countries for which data exist. The bottom 5 percent of children rank higher than the bottom 5 percent in only three countries-South Africa, Ghana and Saudi Arabia. But not all students test poorly. Inequality in the test-score distribution for both states is next only to South Africa in the worldwide ranking exercise. Consequently, and to the extent that these two states can represent India, the two statements "for every ten top performers in the United States there are four in India" and "for every ten low performers in the United States there are two hundred in India" are both consistent with the data. The combination of India's size and large variance in achievement give both the perceptions that India is shining even as Bharat, the vernacular for India, is drowning. Comparable estimates of inequalities in learning are the building blocks for substantive research on the correlates of earnings inequality in India and other low-income countries; the methods proposed here allow for independent testing exercises to build up such data by linking scores to internationally comparable tests.